Learners' Language Needs Analysis of English Subject in Azkia Integrated Islamic Primary School - Neneng Sunengsih; Ahmad Fahrurrozi (IJEE (Indonesian Journal of English Education), 2015)
In this paper, the writer analyzed the objective of English learning at Azkia Integrated Islamic Primary School and the pupils’ needs in learning English. The paper described pupils’ needs, which are divided into the target needs and the learning needs. The study employed qualitative method, which used phenomenology approach. The data were collected from classroom observations, interviews, and documentary analysis, and then were analyzed and classified into the target needs and the learning needs. The findings showed that the pupils’ needs to be fulfilled in learning English are introducing English at the early stage, coping English language in the classroom and the daily lives, emphasizing vocabulary building and its development, applying recognizable topics to support vocabulary mastery, giving a wide range of instruments which stimulates the pupils using English in their daily lives. Further, learning English can be easier for the pupils when the concrete objects  are utilized well and visual aids are made available.